LITERATURE REVIEW: TEHNIK RELAKSASI NAFAS TERHADAP PENURUNAN NYERI DISMINORE - Arum Meiranny; Ariska Afrianti (Poltekkes Kemenkes Medan, 2021)
Dysminorrhea is a complaint that often makes young women go to the doctor for consultation and get treatment. Dysminorrhea is pain that causes discomfort in the lower abdominal area that occurs during menstruation, even dysminorrhea can interfere with daily activities, dysminorrhea often occurs in women who are menstruating. When a woman is menstruating, it produces excess prostaglandins which can cause dysminorrhea pain. Dysminorrhea is a disorder that often occurs during menstruation. Although dysminorrhea is not dangerous, it often disrupts activity patterns in women who are menstruating. The prevalence of dysminorrhea shows a high enough frequency. According to WHO, about 16.8-81% of young women experience dysminorrhea. One of the non-pharmacological therapies is to relax the breath in women who experience dysminorrhea to reduce pain. Methods: international literature and national literature searched through electronic media with keywords. Five articles were selected, each of which represented an effectiveness of breath relaxation on the reduction of dysminore pain. Result: there is an effect of breath relaxation on the reduction of dysminore pain in respondents. Discussion: one of the non-pharmacological treatments to reduce dysminore pain is by breathing relaxation techniques. Breath relaxation can relax muscle tension so that it can reduce pain.